Synthesis of biochar@α-Fe2O3@Shewanella loihica complex for remediation of soil contaminated by hexavalent chromium: Optimization of conditions and mechanism. (September 2022) - Zou, Dexun; Tong, Jingjing; Feng, Chenyu; Wang, Yang; Li, Xinxin; Zheng, Xusheng; Wang, Xuebo; Liu, Yanping
Abstract: The reduction of hexavalent chromium combined with the process of dissimilatory iron reduction is an important strategy for microbial remediation of chromium-contaminated soil. However, its applicability is limited by the slow speed of bacterial bioreduction and the toxic effect of heavy metals on bacteria. Here, biochar (BC) was used as a substrate and was loaded with iron oxide in the form of hematite and Shewanella loihica to synthesize a BC@α-Fe2 O3 @ S. loihica complex and thus achieve combined microbial–chemical remediation. After optimization by a Box–Behnken design, the optimal dosages of the complex, humic acid (as an electron shuttle), and sodium lactate (as an electron donor) were found to be 1.38 mL/g, 33.94 mg/g, and 12.95%, respectively. The Cr(VI) reduction rate in soil contaminated with 1000 mg/kg Cr(VI) reached 98.26%, and remediation could be achieved within 7 days. Characterization of the BC@α-Fe2 O3 @ S. loihica complex before and after it was used for remediation by energy-dispersive X-ray spectroscopy, X-ray diffraction, X-ray photoelectron spectroscopy, and Fourier transform infrared spectroscopy proved that the oxygen-containing functional groups and aromatic compounds on the surface of the BC participated in the adsorption and reduction of Cr(VI) and that the loaded hematite particles were fully utilized by microorganisms. Therefore, the BC@α-Fe2 O3 @ S. loihica complex has great potential for the remediation of Cr(VI)-contaminated soil. Graphical abstract: Image 1 Highlights: The BC@α-Fe2 O3 @ loihica can make the 1000 mg/kg Cr (VI) reduction rate reach 98.26% within 7 days. Iron oxide and electron shuttle have obvious synergistic enhancement in biological reduction. Complex restoration can reduce soil biological toxicity and improve soil community structure.